Draught animal power for land-use intensification in the Ethiopian highlands - Astatke, A.; Mohamed-Saleem, M.A. (1996)
Animal traction has been an integral part of most agricultural systems in Ethiopia for thousands of years. There is evidence that cattle were first used for ploughing in the latter part of the third millennium BC (Goe and Astatke, 1989). Today, the traditional cattle economy is directed mainly towards supplying draught oxen. Ethiopia has a cattle population of 31 million head (FAO, 1994), the largest in Africa, of which 9 to 10 million are used for draught purposes. Zebu oxen are the main work animals and, in pairs, they are primarily used for seed-bed preparation and threshing. Where oxen are in short supply, horses, mules and donkeys are paired with the same species or with others to plough the land. All three equine species are used for transport in most parts of the country. In the lower highlands (below 1 500 masl) and drier regions, camels are used exclusively as pack and transport animals. Where crops and livestock are integrated, crop residues provide the major share of livestock feed. The main livestock outputs are milk, meat, hides, manure and draught power. Livestock are also an economic asset, providing financial security to smallholder farmers. The human population of Ethiopia is 57 million and is growing at the rate of 3.4 percent annually (World Bank, 1993). During the last two decades, the country was hit by two famines. The first, in 1973/74, claimed the lives of 100 000 people, and the second, from 1983 to 1985, was even more devastating, leaving close to 1 million people dead. Also, a considerable number of people were displaced. Although prolonged and consecutive drought years contributed to these famines, the traditional land-use systems cannot support the present population even in normal rainfall years. More food is required if famine is to be avoided in the future. In this paper a sample of alternative uses of animal traction as possible means of intensifying crop production in some farming areas and the obstacles encountered in the transfer of traction technologies are discussed.